Efficacy of amendments to improve soil physical properties at an abandoned lead and zinc mine. Issue 1 (27th May 2020) - Alghamdi, A.; Presley, D.R.; Kirkham, M.B.; Hettiarachchi, G.
Abstract: Relatively little information exists for the long‐term soil physical characteristics of revegetated heavy‐metal mine wastes, particularly several years after reclamation. A large area mined for Pb and Zn from the 1870s to the 1970s is located in the central United States in the Tri‐State Mining District that extends across southeastern Kansas, southwestern Missouri, and northeastern Oklahoma. Seven treatments were established in 2006 on two different sites (called Site A and Site B) near the town of Galena, KS, to study the effect of soil amendments on heavy metal bioavailability. Treatments included a non‐amended control, two different rates of compost, and combinations of compost, lime, and bentonite. The soil physical properties were not measured in 2006. In November 2014, 8.5 yr after the addition of the amendments, the plots were resampled, and water content, bulk density, unsaturated hydraulic conductivity, and wet and dry aggregate stability were measured. Significant treatment effects of the amendments were observed 8.5 yr after treatment establishment, especially at Site B. The water content, bulk density, and hydraulic conductivity parameters had significant treatment differences at Site B, but no one treatment consistently improved soil physical properties. For the dry‐aggregate size distribution test, the control and high compost‐rate treatments at Site B had the greatest fraction of <0.84 mm dry aggregates, and the plots with bentonite had the least, indicating that plots with clay amendments might be most effective for controlling wind erosion for multiple years post‐reclamation.